Orality in administrative sanctioning procedures: foundation and proposals for its improvement - Barrera Pérez, Angiela Paola (2020)
The article aims to analyze how the guarantee of orality operates in administrative sanctioning procedures in Peru. In this sense, the advantages and disadvantages of writing and orality are studied; Subsequently, the regulation of sector regulations regarding orality in administrative sanctioning procedures is analyzed. Finally, basic proposals are proposed to establish a homogeneous criterion that rests on a rule of general application that alows the development of the guarantee of orality.